Ataxia with oculomotor apraxia type 2 caused by a novel homozygous mutation in SETX gene, and literature review - Chen, Shuaishuai; Du, Juping; Jiang, Huihua; Zhao, Weibo; Wang, Na; Ying, Anna; Li, Jun; Chen, Shiyong; Shen, Bo; Zhou, Yuanlin (Frontiers in Molecular Neuroscience, 2022)
Objectives: Autosomal recessive inherited ataxia with oculomotor apraxia 2 (AOA2), caused by SETX gene mutations, is characterized by early onset, progressive cerebellar ataxia, peripheral neuropathy, oculomotor apraxia, and elevated serum α-fetoprotein (AFP). This study aimed to expand and summarize the clinical and genetic characteristics of SETX variants related to AOA2. Methods: The biochemical parameters, electromyogram, and radiological findings of the patient were evaluated. Whole-exome sequencing (WES) was performed on the patient using next-generation sequencing, the variants were confirmed by Sanger sequencing and the pathogenicity of the variants was classified according to the ACMG/AMP guidelines. We reviewed 57 studies of AOA2 patients with SETX mutations and collected clinical and genetic information. Results: The patient was a 40-year-old Chinese woman who primarily presented with numbness and weakness of the lower limbs in her teenage years. She had elevated AFP, increased serum follicle-stimulating hormone (FSH) and luteinizing hormone (LH) and decreased anti-Müllerian hormone (AMH) levels. We identified a novel homozygous missense mutation of the SETX gene, c.7118 C>T (p. Thr2373Ile), in the patient via Whole-exome and Sanger sequencing. The variant was located in the DNA/RNA helicase domain and is highly conserved. The protein prediction analysis verified the SETX variant as a damaging alteration and ACMG/AMP guidelines classified it as likely pathogenic. Through a literature review, we identified 229 AOA2 cases with SETX variants, and among the variants, 156 SETX variants were exonic. We found that 107 (46.7%) patients were European, fifty (21.8%) were African, and forty-eight (21.0%) were Asian. Among the Asian patients, five from two families were Mainland Chinese. The main clinical features were cerebellar ataxia (100%), peripheral neuropathy (94.6%), cerebellar atrophy (95.3%) and elevated AFP concentration (92.0%). Most reported SETX mutations in AOA2 patients were missense, frameshift and nonsense mutations. Conclusion: We discovered a novel homozygous variant of the SETX gene as a cause of AOA2 in the current patient and expanded the genotypic spectrum of AOA2. Moreover, the clinical features of AOA2 and genetic findings in SETX were assessed in reported cohorts and summarized in the present study.